Spin‐Glass State above Room Temperature in a Layered Nickelate Lan+1NinO3n+1. (2nd March 2022) - Song, Chuangye; Li, Xuanyi; Meng, Fanqi; Zhang, Qinghua; Ma, Ji; Guo, Tengyu; Zhang, Yuelin; Zhou, Song; Gu, Lin; Meng, Sheng; Wu, Kehui
Abstract: Oxide interfaces provide a fertile ground for new forms of magnetic textures that arise from different symmetry constraints, proximity effects, and charge transfer. Here, a room‐temperature spin glass state stabilized in heterostructures of the ferromagnetic metallic oxide La2/3 Sr1/3 MnO3 (LSMO) and the layered La n +1 Ni n O3 n +1 (L‐LNO) is reported. Electron energy loss spectra and depth‐profile X‐ray photoelectron spectroscopy reveal the interfacial electron transfer from Mn 3+ to localized Ni 3+ states. Density functional theory calculations indicate that charge transfer drives the enhancement of ferromagnetic exchange interaction in the nickelate, leading to the formation of local magnetic order. The room temperature spin‐glass state in this artificially engineered LSMO/L‐LNO bilayer structure affords opportunities for designing emergent topological spin textures and spintronic devices. Abstract : Room‐temperature spin glass state stabilized in the layered La n +1 Ni n O3 n +1 (L‐LNO) is realized via interfacial engineering with the ferromagnetic metallic oxide La2/3 Sr1/3 MnO3 (LSMO). The discovery of room temperature spin‐glass state in this artificially engineered LSMO/L‐LNO bilayer structure affords opportunities for designing emergent topological spin textures and spintronic devices.